Ezekiel : a commentary based on Iezekiēl in Codex Vaticanus - Olley, John W. 1938- (Septuagint Commentary Series., 2009)
This work is the first major commentary to focus on the text of LXX Ezekiel in any modern language. Rather than seeing LXX mainly as a text-critical resource with variants to be explained, this commentary, as part of the Septuagint Commentary Series, examines a specific manuscript in its own right as a document used by Greek readers unfamiliar with Hebrew. Included are transcription and English translation of Codex Vaticanus, the oldest extant manuscript of the whole book, and a detailed commentary that also compares the earlier P967 and the Masoretic Text where they differ. Another major new contribution is the utilisation of the sense-delimitation (paragraphs) of Codex Vaticanus itself, exploring how this influences reading of the text.